2006
DOI: 10.1182/blood-2006-05-018697
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of erythropoiesis in malarial anemia is associated with hemozoin in vitro and in vivo

Abstract: Malarial anemia is a global public health problem and is characterized by a low reticulocyte response in the presence of life-threatening hemolysis. Although cytokines, in particular tumor necrosis factor-␣ (TNF-␣), can suppress erythropoiesis, the grossly abnormal bone marrow morphology indicates that other factors may contribute to ineffective erythropoiesis. We hypothesized that the cytotoxic hemozoin (Hz) residues from digested hemoglobin (Hb) significantly contribute to abnormal erythropoiesis. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
161
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 52 publications
13
161
2
1
Order By: Relevance
“…A second possible factor that may also exert an influence in erythropoiesis is the production of immune mediators, by host cells, as a response to parasite products; when released, these mediators would damage surrounding haematopoietic cells, altering their morphology and function (82). In this regard, it has been demonstrated that the presence of hemozoin, a metabolic product generated during the digestion of hemoglobin, in plasma, leukocytes, or erytroid precursors, was able to inhibit erythropoiesis (89). Studies conducted with bone marrow sections obtained from children who died as a result of severe malaria showed an association between the amount of hemozoin and the proportion of abnormal erythroid cells (90).…”
Section: Dyserythropoiesis and Immune-mediated Anemiamentioning
confidence: 99%
“…A second possible factor that may also exert an influence in erythropoiesis is the production of immune mediators, by host cells, as a response to parasite products; when released, these mediators would damage surrounding haematopoietic cells, altering their morphology and function (82). In this regard, it has been demonstrated that the presence of hemozoin, a metabolic product generated during the digestion of hemoglobin, in plasma, leukocytes, or erytroid precursors, was able to inhibit erythropoiesis (89). Studies conducted with bone marrow sections obtained from children who died as a result of severe malaria showed an association between the amount of hemozoin and the proportion of abnormal erythroid cells (90).…”
Section: Dyserythropoiesis and Immune-mediated Anemiamentioning
confidence: 99%
“…For a more detailed study on the changes in erythropoietin and severity of anemia during infection with P falciparum see Casals-Pascual. 72 NR indicates not reported. *Hb levels reported in this study were given as a percent of baseline values determined in noninfected mice.…”
Section: Loss Of Uninfected Erythrocytesmentioning
confidence: 99%
“…72 Moreover, bone marrow sections from children who died from severe malaria show a significant association between the quantity of hemozoin (located in erythroid precursors and macrophages) and the proportion of erythroid cells that was abnormal. These findings are consistent with a direct inhibitory effect of hemozoin on erythropoiesis and therefore warrant further investigation.…”
Section: Erythropoietic Suppression and Dyserythropoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, as antiretroviral therapy is increasingly available in sub-Saharan Africa; future studies among such children would be needed. It is noteworthy that the role of hemozoin in malaria pathogenesis, including PCM, has been extensively studied [15][16][17]. A recent multisite study of 26,000 pediatric malaria cases in sub-Saharan Africa concluded that PCM, while predictive of severe disease and mortality, failed to provide additional prognostic value beyond conventional markers of disease severity [18].…”
Section: Moving Toward Hematological Predictors Of Disease Severity Imentioning
confidence: 99%